Post Rebuilding Brand Presence Post-Hacking: A Social Media Strategy for The Seiryu Villas Seminyak - Putri, Ni Putu Widya Maheswari Karantika; Damayanti, Titien; Utama, I Putu (E-Journal of Tourism; Volume 11 Number 2 (September 2024), 2024)
This study examines the use of social media to enhance brand awareness in the hospitality industry, focusing on The Seiryu Villas Seminyak. In the era of the Fourth Industrial Revolution, information and communication technology, particularly social media, has become a strategic tool for hotels to expand their marketing reach and build relationships with customers. This study highlights the importance of online presence and how social media can increase brand awareness, customer loyalty, and a positive image. Through qualitative research methods involving interviews, observations, and documentation studies, this research describes the social media strategies used by The Seiryu Villas before and after the hacking incident of their Instagram account at the end of 2022. The findings show that despite a drastic decline in followers, efforts to rebuild the digital presence through relevant and interactive content continued. This study provides recommendations for integrated marketing strategies to improve the situation, including account security measures and collaborations with influencers, to enhance brand awareness and business growth of The Seiryu Villas on social media platforms.